Implementation of Islamic Senior Hight School Academic Quality Assurance (Multi-Site Study at Islamic Senior High School of Surabaya and Islamic Senior High School of 2 Malang) - Andiek Widodo; Yatim Riyanto; Erni Roesminingsih (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study aims to examine the implementation of academic quality assurance, as well as the strategies and models used in improving academic quality assurance in the Islamic Senior High School of Surabaya and Islamic Senior High School of 2 Malang. This study used a qualitative approach with a multi-site research design. Based on the results of the research that has been done, it is concluded that the implementation of academic quality assurance in the process of implementing education at Madrasahs has been carried out well in improving the quality of learning, academic achievement, and competitiveness of these madrasah graduates. The implementation of quality assurance can be done using the first strategy, the leadership has given trust and responsibility in implementing management guidelines, second, the madrasah activity program is socialized intensively, and third, the preparation of learning tools that are carried out collaboratively. Overall, the implementation of madrasah academic quality assurance has been carried out according to national education standards.